AKULTURASI BUDAYA DALAM ANIME DEAIMON - Nurapipah, Siti; Susanti, Helen (IDEA : Jurnal Studi Jepang, 2024)
This research discusses about the Akulturasi Budaya alam Anime Deaimon. This research used a qualitative descriptive method and a visual approach analysis by describing something to be analyzed using imager that show cultural acculturation in Wagashi and celebration. The theory used in this thesis is cultural elements by Koentjaraningrat and the acculturation strategy by Berry. The results of this thesis can be seen that there is cultural acculturation in the Deaimon anime in Halloween wagashi, Christmas wagashi, Birthday wagashi, Valentine's wagashi, and taiyaki which are included in the integration acculturation strategy. Apart from that, it is known that there are Halloween, Christmas, New Year and Valentine's celebrations which are included in the acculturation strategy of assimilation and separation.